Caminhos do desenvolvimento sustentável: proposta para a reflexão sobre a cultura do consumo - Lima, Victória Benício (2022)
Sustainable Development has been widely publicized in the various spaces of discussion in view of the need for actions that reduce the socio-environmental impacts generated by the model of consumerist society that humanity generated in the search for economic growth and is sustained until today. The most accepted definition today is a development that allows humanity to meet the needs of the current and future generations, enabling everyone to have a quality life and the maintenance of the environment that provides the means of survival, to be conserved to continue providing capital. natural resource we need, assuming that we cannot deplete ecosystem resources in favor of life. This work aimed to develop an educational product that could serve as a reflective guide on consumer culture and its current scenario, with high school students, seeking to awaken the importance of these subjects in the social space and add value to environmental discussions that promote sustainability by building the notions of Development and Sustainable Consumption as a theoretical category through the experiences of students with means of support for discussions regarding environmental conservation and changing consumer habits. A qualitative methodological approach was used, in an attempt to infer in the subject a transformative look at the subject that would incorporate meaning to their experiences, through participatory action research as an alternative to traditional forms of knowledge production, giving space for action and participation. This research was applied at Colégio Estadual Imaculada Conceição – Cafarnaum/Bahia, with high school classes. Interdisciplinary activities were developed that involved students in their own experiences and social relationships regarding the Consumer Society. A questionnaire that made it possible to see the students' preliminary knowledge on the subject, a workshop that served as a space for the construction of knowledge, the necessary discussions and the reflection of the consumption structures in which today's society sees itself inserted with the production of materials that not only, enable the teaching and learning process as well as affirm the importance of criticality and sustainable action in the face of consumerist habits and finally a Podcast with external agents who use their speech spaces to dialogue about Sustainable Development and its multiple paths. The results showed the importance of approaching the research topic from its conceptual construction to the possibilities of confrontation that would give rise to economic, political, historical, sociocultural and above all environmental relationships. The students produced materials during the process that expressed the construction of the knowledge carried out in the process, which allowed them to follow the learning process, understanding how the next step could be approached without creating gaps that would make it impossible to construct the arguments offered in the course. route. Among the educational products produced in the course of the research, the workshop “Building Ideas” served as an indicative for the discussion of the consumer society, brought, among other strategies, the Ecological Footprint as a resource for reflection and the SWOT analysis as a planning tool to replicate the workshop in other spaces and the “Consuming Ideias” Podcast that addressed various topics from the perspective of sustainable consumption, strengthening the dialogue between different actors in the region, presenting a direct relationship with the students' experiences. The latter represented an approximation between the school and the community and allowed the dialogue to be brought closer to those who most need to fight in favor of sustainability and the right social conditions.